Influence of iron mass on Cr isotope fractionation associated with Cr(VI) reduction by zero-valent iron - Filip Budimir; Richard T. Amos; Carol J. Ptacek; David W. Blowes (Journal of Contaminant Hydrology, 2026)

Overcoming size barriers in retinal gene therapy via lipid nanoparticle-mediated delivery of full-length eys DNA - Sarah Goddaer; Emma De Coster; Elise Callens; Emma Van Caenegem; Olivier Van den Heule; Rob W. J. Collin; Karen Peynshaert; Filip Van Nieuwerburgh; Kevin Braeckmans; Katrien Remaut (Drug Delivery and Translational Research, 2026)

From lipofuscin accumulation to cellular dysfunction: a focus on liver pathophysiology - Filip Braet; Eddie Wisse; Ger H. Koek; Gerald J. Shami; Amy Li (Histochemistry and Cell Biology, 2026)
In this review, we summarize the data on the cellular pigment lipofuscin that accumulates in liver tissue over time, due to aging and cellular stress. Despite the presence of these typical subcellular inclusions under various conditions, relatively little is known about their origins, roles, and effects on liver cell and tissue health. Pathologists use the presence of lipofuscin, in combination with other markers, to achieve differential diagnosis across various diseases. Routine histological stains reveal characteristic irregular shaped intracellular inclusions of lipofuscin that cannot be missed. Moreover, lipofuscin is autofluorescent and in transmission electron microscopy it appears in the cytoplasm as irregularly shaped structures containing fat and floccular material with varying electron density. Herein, we discuss the current state of knowledge concerning the origin and function of this pigment in the liver. Lipofuscin can distinctively be found in liver, although it has also been reported in cells in the heart, brain, and eye. Its biochemical composition is heterogeneous and varies depending on the tissue and the age of the organism. The liver parenchymal cells have efficient cellular waste disposal mechanisms, but they are still susceptible to aging. Lipofuscin accumulation in the liver may result from ongoing oxidative damage and impaired hepatic detoxification leading to cellular stress.

Cellular accumulation of lipofuscin in the heart: implications in health and disease - Amy Li; Sean Lal; Gerald J. Shami; Kenneth S. Campbell; Eddie Wisse; Filip Braet (Histochemistry and Cell Biology, 2026)
Lipofuscin is a subcellular pigmented granule that has long been considered a sign of wear-and-tear and aging. This granule cannot be degraded but may be diluted by cell division. In the heart, lipofuscin can be easily identified in cardiomyocytes where proliferative capacity is limited, and to a lesser extent in other cardiac cell types, by their characteristic morphological features. They appear as yellow–brown granules in histopathology sections reflecting their lipid origins, and as heterogenous membrane-bound bodies containing a mix of lipid and electron-lucent content in transmission electron microscopy. Lipofuscin was originally considered a mere byproduct of age-related cell senescence but studies over the past three decades have indicated that its role and mechanism of formation may be far more complex. In this review, we examine how lipofuscin is formed and its implications in aging and diseases of the heart. While the focus of this review is on lipofuscin in the two most predominate cell types of the heart, cardiomyocytes and fibroblasts, we also touch on the presence of lipofuscin in the vasculature in certain disease phenotypes that are directly relevant to cardiovascular health.

From food to sewer: Dietary inputs support the temporal and population-wide stability of pepper mild mottle virus in wastewater - Sofia Persson; Javier Edo Varg; Sarah Coker; Fanny Persson; Filip Petrini; Israa Dafalla; Lauren Davies; Polina Vaulina; Monika Vilemova; Nahla Mohamed; Maja Malmberg; Anna J. Székely (Water Research, 2026)

Cryptic coral reef microhabitats and the functional role of brittle stars in biogenic sediment generation - D. M. de Bakker; C. T. Perry; L. de Nooijer; A. J. Ramírez-Menéndez; J. E. Lloyd Newman; F. Hale; L. Alvarez-Filip (Coral Reefs, 2026)
Recent studies have highlighted the ecological importance of cryptic habitat space on coral reefs. These microhabitats, ranging from framework cavities to intra-branch space within marine macroalgae, can harbour diverse and ecologically relevant taxa. Here we show that brittle stars, ubiquitous across such cryptic habitats (reported densities exceeding 100 ind. m −2 ), represent an important, but previously neglected, source of skeletal sediment on reefs. Reef-derived carbonate sediment is generated by a range of reef biota and represents a critical geo-ecological process, contributing to reef structural development and vertical accretion via framework infilling, and the development and maintenance of lagoonal and shoreline habitats. Our sediment production estimates are based on skeletal carbonate content data for differently sized specimens of common brittle star morphotypes, combined with field-based density assessments from widespread microhabitat types (framework cavities, sub-rubble space and intra-algal skeletal branches) on Mexican Caribbean reefs. Resulting estimates suggest that brittle stars can make substantial contributions to reef sediment production (averaging 110 g m⁻ 2 yr⁻ 1 ; 95% CI 59–161). Spine-bearing taxa contribute disproportionately due to their high skeletal mass (> 6 g in large individuals) and high abundance (accounting for over 80% of sub-rubble populations). Resultant biogenic sediments are high-Mg calcite (15.6 ± 0.1 mol% MgCO₃) and predominantly disarticulate into fine to coarse-grained sand material (125 µm–2 mm). These findings highlight the underappreciated role of brittle stars in reef carbonate cycling. With many reef systems undergoing rapid changes in benthic ecology and microhabitat space availability, identifying and characterising links to biogenic sediment sources is central to understanding future reef sediment production regimes.

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Proceedings of the 2024 FDA-CRCG Workshop: Scientific and Regulatory Considerations for Assessment of Immunogenicity Risk for Generic Peptide and Oligonucleotide Drug Products - Jennifer K. Lee; Ha-Na Lee; Sudhir Agrawal; Joseph A. Balsamo; Andrew Clerman; Sofie Denies; Anne De Groot; Jeremy Fry; Nicolas Gaudenzio; Andrew J. Graves; Kristina E. Howard; SuJin Hwang; et al. (The AAPS Journal, 2026)

Alchemilla vulgaris L. inhibits EMT and suppresses migration and invasion in triple-negative breast cancer - Aleksandra G. Nikezić; Jovana V. Jovankić; Danijela D. Nikodijević; Milena G. Milutinović; Zorana Z. Dobrijević; Filip J. Grbović; Nenad L. Vuković; Milena D. Vukić; Danijela M. Cvetković (South African Journal of Botany, 2026)

Repellency of Urtica dioica (Urticaceae) and Erigeron annuus (Asteraceae) to Plodia interpunctella (Lepidoptera: Pyralidae) larvae - Dragana Z. Predojević; Filip J. Grbović; Filip N. Vukajlović; Snežana B. Pešić (International Journal of Tropical Insect Science, 2026)

On the long-term storage of tissue for fluorescence and electron microscopy: lessons learned from rat liver samples - Gerald J. Shami; Zenan Chen; Delfine Cheng; Eddie Wisse; Filip Braet (Histochemistry and Cell Biology, 2025)
Occasionally, tissue samples cannot be processed completely and are stored under varying conditions for extended periods. This is particularly beneficial in interinstitutional studies where a given research setting may lack the expertise or infrastructure for sample processing, imaging and data analysis. Currently, there is limited literature available on the controlled storage of biological tissues in primary fixatives for fluorescence and electron microscopy. In this contribution, we mimicked various tissue storage scenarios by taking different fixation conditions, storage temperatures and storage durations into account. Rat liver tissue was used for its well-known diversity of cellular ultrastructure and microscopy analysis. Fluorescent labelling of actin, DNA and lipids were employed in conjunction with high-resolution electron microscopy imaging. Herein, we tested three different fixative solutions (1.5% glutaraldehyde, 0.4% glutaraldehyde and 4% formaldehyde and 4% formaldehyde) and stored samples for 1–28 days at room temperature and refrigerator temperature. We found that liver tissue can be stored for up to 2 weeks in a 0.4% glutaraldehyde + 4% formaldehyde fixative solution, while still enabling reliable fluorescent labelling and ultrastructural studies. Ultrastructural integrity was eminent up to 1 month using either glutaraldehyde or formaldehyde fixation protocols. When liver tissue is fixed with a mixture of 0.4% glutaraldehyde and 4% formaldehyde and stored at 4 °C, it retains its capacity for electron microscopy analysis for several years, but loses its capacity for reliable fluorescent labelling studies. In conclusion, we demonstrated that liver tissue can be stored for extended periods enabling profound structure–function analysis across length scales.

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Hazardous metals coupled with increasing summer diurnal temperature range contributed to growth decline of two oak species in a heavily industrialized area - Constantin Nechita; Andreea Maria Iordache; Tomas Pluhacek; Filip Gregar; J. Julio Camarero (Journal of Hazardous Materials, 2025)

Surface temperature changes indicate disease onset after pulmonary murine corona virus infection, but do not constitute a humane endpoint - Rebecca Nistelberger; Patrizia Gibler; Thomas Filip; Manuel Salzmann; Boris Hartmann; Bruno K. Podesser; Roberto Plasenzotti; Philipp J. Hohensinner; Julia B. Kral-Pointner (Veterinary Research Communications, 2025)
Mouse models are important contributors for understanding the immune system during infections. Objective parameters help to assess the course of infection and guarantee animal welfare. In this study we analyzed if surface temperature measured via thermal imaging of the dorsal area is a suitable marker to evaluate animal wellbeing during murine coronavirus (MCoV) infection. Infected BALB/c mice displayed severe symptoms whereas C57BL/6 mice were less affected. In BALB/c animals, temperature increased from 27.1 °C to 28.4 °C within 24 h with levels remaining slightly elevated over the observation period. In contrast, a decrease in body weight was consistent through the period with 60% of the animals reaching the previously set termination point of 20% weight loss ( n = 6). Also, C57BL/6J animals showed a significant temperature increase from 27.1 °C to 28.4 °C within 24 h and a significant weight loss over time with two out of ten reached weight loss end point. However, temperature and weight changes were not related in individual animals. In contrast to temperature values, body weight clearly set a trajectory towards early termination. Taken together, our data indicate that superficial temperature did not serve as a predictive parameter for defining humane end points, but indicate disease onset after pulmonary virus infection.

Navigating yeast selection for NABLAB production: Comparative study of commercial maltose- and maltotriose-negative strains - Elia Myncke; Dana Vanderputten; David Laureys; Joren Huys; Johanna Schlich; Filip Van Opstaele; Joachim J. Schouteten; Jessika De Clippeleer (Food Chemistry, 2025)

Trophic Interactions Are Key to Understanding the Effects of Global Change on the Distribution and Functional Role of the Brown Bear - Pablo M. Lucas; Wilfried Thuiller; Lauren Talluto; Ester Polaina; Jörg Albrecht; Nuria Selva; Marta De Barba; Vincenzo Penteriani; Maya Guéguen; Niko Balkenhol; Trishna Dutta; Ancuta Fedorca; et al. (Global Change Biology, 2025)
Biotic interactions are expected to influence species' responses to global changes, but they are rarely considered across broad spatial extents. Abiotic factors are thought to operate at larger spatial scales, while biotic factors, such as species interactions, are considered more important at local scales within communities, in part because of the knowledge gap on species interactions at large spatial scales (i.e., the Eltonian shortfall). We assessed, at a continental scale, (i) the importance of biotic interactions, through food webs, on species distributions, and (ii) how biotic interactions under scenarios of climate and land‐use change may affect the distribution of the brown bear ( Ursus arctos ). We built a highly detailed, spatially dynamic, and empirically sampled food web based on the energy contribution of 276 brown bear food species from different taxa (plants, vertebrates, and invertebrates) and their ensemble habitat models at high resolution across Europe. Then, combining energy contribution and predicted habitat of food species, we modelled energy contribution across space and included these layers within Bayesian‐based models of the brown bear distribution in Europe. The inclusion of biotic interactions considerably improved our understanding of brown bear distribution at large (continental) scales compared with Bayesian models including only abiotic factors (climate and land use). Predicted future range shifts, which included changes in the distribution of food species, varied greatly when considering various scenarios of change in biotic factors, providing a warning that future indirect climate and land‐use change are likely to have strong but highly uncertain impacts on species biogeography. Our study confirmed that advancing our understanding of ecological networks of species interactions will improve future projections of biodiversity change, especially for modelling species distributions and their functional role under climate and land‐use change scenarios, which is key for effective conservation of biodiversity and ecosystem services.

Inactive “Ghost” Cells Do Not Affect Motility and Long‐Range Electron Transport in Filamentous Cable Bacteria - Jesper R. van Dijk; Jeanine S. Geelhoed; Nicole Geerlings; Jiji Alingapoyil Choyikutty; Henricus T. S. Boschker; Erik Verbruggen; Filip J. R. Meysman (Environmental Microbiology, 2025)
Cable bacteria are multicellular filamentous microorganisms that perform electrogenic sulphur oxidation over centimetre‐long distances. These filaments contain so‐called “ghost cells”, which display a highly reduced cytoplasmic content and a lack of metabolic activity. However, the origin and abundance of these ghost cells are not well understood, raising questions about their formation and potential impact on the functioning of the entire filaments. Here, we quantified the abundance of ghost cells in cable bacteria via a targeted propidium iodide staining technique and investigated their morphology and possible origin. Microscopy revealed that ghost cells are present in filaments under in situ conditions, and hence, they are not an artefact from filament sampling. Interestingly, filaments containing ghost cells retained gliding motility, as well as the capacity for long‐distance electron transport, thus suggesting that the functionality of the filament as a whole remains largely unaffected by the presence of these ghost cells. Noteworthy is the higher frequency of ghost cells near the ends of filaments, and within filament fragments retrieved from oxic environments. Our findings provide new insights into the adaptive strategies of filamentous bacteria, highlighting their ability to maintain functionality at the organism level despite the fact that some individual cells are no longer metabolically active.

Hyperplex PCR enables highly multiplexed analysis of point mutations in wastewater: Long-term SARS-CoV-2 variant surveillance in Sweden as a case study - Ruben R.G. Soares; Javier Edo Varg; Attila Szabó; Mariana Kluge; Filip Petrini; Margarita Psallida; Paweł Olszewski; Danai V. Nikou; Isaac Owusu-Agyeman; Mariel Perez-Zabaleta; Zeynep Cetecioglu; Umear Naseem; et al. (Water Research, 2025)

The Roles of Secondary Calcifiers in Reef Construction and Maintenance in Coral and Rocky Reefs of the Mexican Pacific - Sandra Pareja‐Ortega; Rafael A. Cabral‐Tena; Alma Paola Rodríguez‐Troncoso; Lorenzo Álvarez‐Filip; Luis E. Calderon‐Aguilera; J. Adán Avilés‐Chávez; Raquel Negrete‐Aranda; Amílcar L. Cupul‐Magaña (Marine Ecology, 2025)
Carbonate production by sclerobionts was quantified with calcification‐accretion units (CAUs) to evaluate the roles of different taxonomic groups in the construction and maintenance of coral reef structures in two sites in the Mexican Pacific with contrasting environmental characteristics: Yelapa and Isla Espíritu Santo (IES). Five CAUs were collected every 6 months for 2 years. The average calcification rate in Yelapa and IES was 1.04 ± 0.11 kg m −2 year −1 and 1.01 ± 0.82 kg m −2 year −1 ; no difference in calcification was found between sites ( H = 0.13, df = 1, p = 0.71), although significant differences in calcification were found over time ( H = 9.13, df = 3, p = 0.03). Barnacles exhibited the highest calcification rate (Yelapa: 0.63 ± 0.8 kg CaCO 3 m −2 year −1 ; IES: 0.54 ± 0.6 kg CaCO 3 m −2 year −1 ), followed by mollusks (Yelapa: 0.27 ± 0.35, IES: 0.18 ± 0.26 kg CaCO 3 m −2 year −1 ), crustose coralline algae (CCA) (Yelapa: 0.025 ± 0.029 kg CaCO 3 m −2 year −1 ; IES: 0.08 ± 0.11 kg CaCO 3 m −2 year −1 ), and bryozoans (Yelapa: 0.04 ± 0.06 kg CaCO 3 m −2 year −1 ; IES: 0.11 ± 0.11 kg CaCO 3 m −2 year −1 ). Cover was dominated by barnacles (27.7%), CCA (16.5%), and mollusks (13.7%) in Yelapa and by bryozoans (27.9%), CCA (20.4%), and barnacles (17.4%) in IES. The coverage of all groups (except CCA) was different between sites, and all taxonomic groups (except foraminifera) exhibited differences over time. The role of each taxonomic group was attributed according to their substrate preference (exposed or cryptic). In Yelapa, bryozoans and polychaetes filled cavities, while CCAs and bryozoans contributed to vertical reef accretion in IES.

Assessment of brain function during stunning and killing of channel catfish (Ictalurus punctatus) - Per Hjelmstedt; Filip To; Peter J. Allen; Albin Gräns (Aquaculture, 2025)

The Impact of Variable DOC Concentrations on Acidification Assessments - Johanna Stadmark; Filip Moldan; Sara Jutterström; Bernard J. Cosby (Ecosystems, 2025)

Titanium dioxide nanoparticles - physicochemical characterization and cytotoxic risk - Filip Kunc; Xiaomei Du; Andre Zborowski; Linda J. Johnston; David C. Kennedy (NanoImpact, 2025)

Chromium isotope fractionation during the removal of hexavalent chromium by oak-based biochar - Filip Budimir; Carol J. Ptacek; Richard T. Amos; David W. Blowes (Chemosphere, 2024)

Clinical and Brain Morphometry Predictors of Deep Brain Stimulation Outcome in Parkinson’s Disease - Maija Koivu; Aleksi J. Sihvonen; Johanna Eerola-Rautio; K. Amande M. Pauls; Julio Resendiz-Nieves; Nuutti Vartiainen; Riku Kivisaari; Filip Scheperjans; Eero Pekkonen (Brain Topography, 2024)
Subthalamic deep brain stimulation (STN-DBS) is known to improve motor function in advanced Parkinson’s disease (PD) and to enable a reduction of anti-parkinsonian medication. While the levodopa challenge test and disease duration are considered good predictors of STN-DBS outcome, other clinical and neuroanatomical predictors are less established. This study aimed to evaluate, in addition to clinical predictors, the effect of patients’ individual brain topography on DBS outcome. The medical records of 35 PD patients were used to analyze DBS outcomes measured with the following scales: Part III of the Unified Parkinson’s Disease Rating Scale (UPDRS-III) off medication at baseline, and at 6-months during medication off and stimulation on, use of anti-parkinsonian medication (LED), Abnormal Involuntary Movement Scale (AIMS) and Non-Motor Symptoms Questionnaire (NMS-Quest). Furthermore, preoperative brain MRI images were utilized to analyze the brain morphology in relation to STN-DBS outcome. With STN-DBS, a 44% reduction in the UPDRS-III score and a 43% decrease in the LED were observed ( p <0.001). Dyskinesia and non-motor symptoms decreased significantly [median reductions of 78,6% (IQR 45,5%) and 18,4% (IQR 32,2%) respectively, p =0.001 – 0.047]. Along with the levodopa challenge test, patients’ age correlated with the observed DBS outcome measured as UPDRS-III improvement ( ρ= -0.466 – -0.521, p <0.005). Patients with greater LED decline had lower grey matter volumes in left superior medial frontal gyrus, in supplementary motor area and cingulum bilaterally. Additionally, patients with greater UPDRS-III score improvement had lower grey matter volume in similar grey matter areas. These findings remained significant when adjusted for sex, age, baseline LED and UPDRS scores respectively and for total intracranial volume ( p =0.0041- 0.001). However, only the LED decrease finding remained significant when the analyses were further controlled for stimulation amplitude. It appears that along with the clinical predictors of STN-DBS outcome, individual patient topographic differences may influence DBS outcome. Clinical Trial Registration Number: NCT06095245, registration date October 23, 2023, retrospectively registered

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Cable bacteria colonise new sediment environments through water column dispersal - Jesper R. van Dijk; Jeanine S. Geelhoed; Philip Ley; Silvia Hidalgo‐Martinez; Miguel Portillo‐Estrada; Erik Verbruggen; Filip J. R. Meysman (Environmental Microbiology, 2024)
Cable bacteria exhibit a unique metabolism involving long‐distance electron transport, significantly impacting elemental cycling in various sediments. These long filamentous bacteria are distributed circumglobally, suggesting an effective mode of dispersal. However, oxygen strongly inhibits their activity, posing a challenge to their dispersal through the water column. We investigated the effective dispersal of marine cable bacteria in a compartmentalised microcosm experiment. Cable bacteria were grown in natural ‘source’ sediment, and their metabolic activity was recorded in autoclaved ‘destination’ cores, which were only accessible through oxygenated seawater. Colonisation occurred over weeks, and destination cores contained only one cable bacterium strain. Filament ‘snippets’ (fragments with a median size of ~15 cells) accumulated in the microcosm water, with about 30% of snippets attached to sediment particles. Snippet release was also observed in situ in a salt marsh creek. This provides a model for the dispersal of cable bacteria through oxygenated water: snippets are formed by filament breakage in the sediment, released into the overlying water and transported with sediment particles that likely offer protection. These insights are informative for broader theories on microbial community assembly and prokaryotic biogeography in marine sediments.

Dynamic population modeling of bacterioplankton community response to gelatinous marine zooplankton bloom collapse and its impact on marine nutrient balance - Filip Strniša; Tinkara Tinta; Gerhard J. Herndl; Gregor Kosec (Progress in Oceanography, 2024)

Is EGD Needed in all Patients after Suicidal or Exploratory Caustic Ingestions? - Michael Levine; Yaron Finkelstein; William J. Trautman; Dazhe Cao; Evan Schwarz; Ari Filip; Leanne Cook; Sameer Arbussattar Pathan; Cherie Obilom; Jim Liu; Joseph Yanta; Neta Cohen; et al. (Journal of Medical Toxicology, 2024)

Quantifying sediment sources, pathways, and controls on fluvial transport dynamics on James Ross Island, Antarctica - Christopher D. Stringer; John F. Boyle; Filip Hrbáček; Kamil Láska; Ondřej Nedělčev; Jan Kavan; Michaela Kňažková; Jonathan L. Carrivick; Duncan J. Quincey; Daniel Nývlt (Journal of Hydrology, 2024)

A new methodology using borehole data to measure angular distances between geological interfaces - Michał P. Michalak; Paweł Marzec; Filip Turoboś; Paulina Leonowicz; Lesław Teper; Paweł Gładki; Michael J. Pyrcz; Mariusz Szubert (Earth Science Informatics, 2023)
The study presents a new triangulation-based workflow to assess the degree of parallelism between geological surfaces. This workflow consists of producing and analyzing angular distance distributions as well as conducting spatial analysis using grid maps applicable for subsurface environments with sparse data. We tested our approach using a set of interfaces from Kraków-Silesian Homocline, a geological unit with preferred subhorizontal dip to NE. The pairs of interfaces for angular distance measurements can be divided into two groups: i) separating only Jurassic homocline-related units and ii) separating Jurassic homocline-related units from homocline-unrelated units. To observe potential differences for these two groups, we used bootstrap methods and estimated confidence intervals for summary statistics. In our case, the mean of angular distances turned out to be in general smaller for the pair separating only homocline-related Jurassic sediments. The results also show that the method can be more sensitive to the identification of small-scale structures which are developed only in some of the analyzed surfaces. We provided open-source and freely available computer code to allow reproducibility of the results.

How spatio-temporal resolution impacts urban energy calibration - Aysegul Demir Dilsiz; Kingsley E. Nweye; Allen J. Wu; Jérôme H. Kämpf; Filip Biljecki; Zoltan Nagy (Energy and Buildings, 2023)

Quantifying soil properties relevant to soil organic carbon biogeochemical cycles by infrared spectroscopy: The importance of compositional data analysis - Pengzhi Zhao; Daniel J. Fallu; Ben R. Pears; Camille Allonsius; Jonas J. Lembrechts; Stijn Van de Vondel; Filip J.R. Meysman; Sara Cucchiaro; Paolo Tarolli; Pu Shi; Johan Six; Antony G. Brown; et al. (Soil and Tillage Research, 2023)

Self-reported intake of high-fat and high-sugar diet is not associated with cognitive stability and flexibility in healthy men - Hendrik Hartmann; Lieneke K. Janssen; Nadine Herzog; Filip Morys; Daniel Fängström; Sean J. Fallon; Annette Horstmann (Appetite, 2023)

A tapt1 knock-out zebrafish line with aberrant lens development and impaired vision models human early-onset cataract - Tamara Jarayseh; Brecht Guillemyn; Hanna De Saffel; Jan Willem Bek; Delfien Syx; Sofie Symoens; Yannick Gansemans; Filip Van Nieuwerburgh; Sujatha Jagadeesh; Jayarekha Raja; Fransiska Malfait; Paul J. Coucke; et al. (Human Genetics, 2023)

Thallium accumulation and distribution in Silene latifolia (Caryophyllaceae) grown in hydroponics - Amelia Corzo Remigio; Philip Nti Nkrumah; Filip Pošćić; Mansour Edraki; Alan J. M. Baker; Antony van der Ent (Plant and Soil, 2022)
Purpose Thallium (Tl) is one of the most toxic elements known and its contamination is an emerging environmental issue associated with base metal (zinc-lead) mining wastes. This study investigated the nature of Tl tolerance and accumulation in Silene latifolia , which has so far only been reported from field-collected samples. Methods Silene latifolia was grown in hydroponics at different Tl concentrations (0, 2.5, 5, 30 and 60 μM Tl). Elemental analysis with Inductively coupled plasma atomic emission spectroscopy (ICP-AES) and laboratory-based micro-X-ray fluorescence spectroscopy (μ-XRF) were used to determine Tl accumulation and distribution in hydrated organs and tissues. Results This study revealed unusually high Tl concentrations in the shoots of S. latifolia , reaching up to 35,700 μg Tl g −1 in young leaves. The species proved to have exceptionally high levels of Tl tolerance and had a positive growth response when exposed to Tl dose rates of up to 5 μM. Laboratory-based μXRF analysis revealed that Tl is localized mainly at the base of the midrib and in the veins of leaves. This distribution differs greatly from that in other known Tl hyperaccumulators. Conclusions Our findings show that S. latifolia is among the strongest known Tl hyperaccumulators in the world. The species has ostensibly evolved mechanisms to survive excessive concentrations of Tl accumulated in its leaves, whilst maintaining lower Tl concentrations in the roots. This trait is of fundamental importance for developing future phytoextraction technologies using this species to remediate Tl-contaminated mine wastes.

Benzonatate Overdose Presenting as Cardiac Arrest with Rapidly Narrowing QRS Interval - Robert J. Stephens; Ari B. Filip; Kevin T. Baumgartner; Evan S. Schwarz; David B. Liss (Journal of Medical Toxicology, 2022)

Species richness and community structure of earthworms (Oligochaeta: Lumbricidae) in natural and agricultural ecosystems - Jovana M. Sekulić; Slobodan N. Milenković; Mirjana M. Stojanović; Filip J. Popović; Tanja B. Trakić (Biologia, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Diversity, ecology, and community structure of the terrestrial diatom flora from Ulu Peninsula (James Ross Island, NE Antarctic Peninsula) - Barbora Chattová; Tereza Cahová; Eveline Pinseel; Kateřina Kopalová; Tyler J. Kohler; Filip Hrbáček; Bart Van de Vijver; Daniel Nývlt (Polar Biology, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The impact of medicinal﻿ plant Ocimum minimum L. on fatty acid synthesis process in breast cancer cells - Jovana V. Jovankić; Danijela M. Cvetković; Milena G. Milutinović; Danijela D. Nikodijević; Aleksandra G. Nikezić; Filip J. Grbović; Nenad L. Vuković; Milena D. Vukić; Dragana Z. Jakovljević; Snežana D. Marković (Biologia, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Fat causes necrosis and inflammation in parenchymal cells in human steatotic liver - Eddie Wisse; Filip Braet; Gerald J. Shami; Bartlomiej Zapotoczny; Celien Vreuls; Pauline Verhaegh; Peter Frederik; Peters J. Peters; Steven Olde Damink; Ger Koek (Histochemistry and Cell Biology, 2022)
Adapted fixation methods for electron microscopy allowed us to study liver cell fine structure in 217 biopsies of intact human livers over the course of 10 years. The following novel observations and concepts arose: single fat droplets in parenchymal cells can grow to a volume four times larger than the original cell, thereby extremely marginalizing the cytoplasm with all organelles. Necrosis of single parenchymal cells, still containing one huge fat droplet, suggests death by fat in a process of single-cell steatonecrosis. In a later stage of single-cell steatonecrosis, neutrophils and erythrocytes surround the single fat droplet, forming an inflammatory fat follicle indicating the apparent onset of inflammation. Also, fat droplets frequently incorporate masses of filamentous fragments and other material, most probably representing Mallory substance. No other structure or material was found that could possibly represent Mallory bodies. We regularly observe the extrusion of huge fat droplets, traversing the peripheral cytoplasm of parenchymal cells, the Disse space and the endothelium. These fat droplets fill the sinusoid as a sinusoidal lipid embolus. In conclusion, adapted methods of fixation applied to human liver tissue revealed that single, huge fat droplets cause necrosis and inflammation in single parenchymal cells. Fat droplets also collect Mallory substance and give rise to sinusoidal fat emboli. Therefore, degreasing of the liver seems to be an essential therapeutic first step in the self-repairing of non-alcoholic fatty liver disease. This might directly reduce single-cell steatotic necrosis and inflammation as elements in non-alcoholic steatohepatitis progression.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Untangling the structural and molecular mechanisms underlying colour and rapid colour change in a lizard, Agama atra - Michaël P. J. Nicolaï; Liliana D’Alba; Jonathan Goldenberg; Yannick Gansemans; Filip Van Nieuwerburgh; Susana Clusella‐Trullas; Matthew D. Shawkey (Molecular Ecology, 2021)
With functions as diverse as communication, protection and thermoregulation, coloration is one of the most important traits in lizards. The ability to change colour as a function of varying social and environmental conditions is thus an important innovation. While colour change is present in animals ranging from squids, to fish and reptiles, not much is known about the mechanisms behind it. Traditionally, colour change was attributed to migration of pigments, in particular melanin. More recent work has shown that the changes in nanostructural configuration inside iridophores are able to produce a wide palette of colours. However, the genetic mechanisms underlying colour, and colour change in particular, remain unstudied. Here we use a combination of transcriptomic and microscopic data to show that melanin, iridophores and pteridines are the main colour‐producing mechanisms in Agama atra , and provide molecular and structural data suggesting that rapid colour change is achieved via melanin dispersal in combination with iridophore organization. This work demonstrates the power of combining genotypic (gene expression) and phenotypic (microscopy) information for addressing physiological questions, providing a basis for future studies of colour change.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Implementing interventions to reduce work-related stress among health-care workers: an investment appraisal from the employer’s perspective - Ben F. M. Wijnen; Joran Lokkerbol; Cecile Boot; Bo M. Havermans; Allard J. van der Beek; Filip Smit (International Archives of Occupational and Environmental Health, 2020)
Purpose The Stress-Prevention@Work implementation strategy has been demonstrated to be successful in reducing stress in employees. Now, we assess the economic return-on-investment to see if it would make for a favourable business case for employers. Methods Data were collected from 303 health-care workers assigned to either a waitlisted control condition (142 employees in 15 teams) or to Stress-Prevention@Work (161 employees in 15 teams). Main outcome was productivity losses measured using the Trimbos and iMTA Cost questionnaire in Psychiatry. Measurements were taken at baseline, 6, and 12 months post-baseline. Results The per-employee costs of the strategy were €50. Net monetary benefits were the benefits (i.e., improved productivity) minus the costs (i.e., intervention costs) and were the main outcome of this investment appraisal. Per-employee net benefits amounted to €2981 on average, which was an almost 60-fold payout of the initial investment of €50. There was a 96.7% likelihood for the modest investment of €50 to be offset by cost savings within 1 year. Moreover, a net benefit of at least €1000 still has a likelihood of 88.2%. Conclusions In general, there was a high likelihood that Stress-Prevention@Work offers an appealing business case from the perspective of employers, but the employer should factor in the additional per-employee costs of the stress-reducing interventions. Still, if these additional costs were as high as €2981, then costs and benefits would break even. This study was registered in the Netherlands National Trial Register, trial code: NTR5527.

The anti-invasive activity of Robinia pseudoacacia L. and Amorpha fruticosa L. on breast cancer MDA-MB-231 cell line - Danijela M. Cvetković; Jovana V. Jovankić; Milena G. Milutinović; Danijela D. Nikodijević; Filip J. Grbović; Andrija R. Ćirić; Marina D. Topuzović; Snežana D. Marković (Biologia, 2019)

Quantitative pixel intensity- and color-based image analysis on minimally compressed files: implications for whole-slide imaging - Douglas J. Taatjes; Nicole A. Bouffard; Taylor Barrow; Katherine A. Devitt; Juli-Anne Gardner; Filip Braet (Histochemistry and Cell Biology, 2019)

Cable bacteria promote DNRA through iron sulfide dissolution - Adam J. Kessler; Michaela Wawryk; Ugo Marzocchi; Keryn L. Roberts; Wei Wen Wong; Nils Risgaard‐Petersen; Filip J. R. Meysman; Ronnie N. Glud; Perran L. M. Cook (Limnology and Oceanography, 2019)
Cable bacteria represent a newly discovered group of filamentous microorganisms, which are capable of spatially separating the oxidative and reductive half‐reactions of their sulfide‐oxidizing metabolisms over centimeter distances. We investigated three ways that cable bacteria might interact with the nitrogen (N) cycle: (1) by reducing nitrate through denitrification or dissimilatory nitrate reduction to ammonium (DNRA) within their cathodic cells; (2) by nitrifying ammonium within their anodic cells; and (3) by indirectly affecting denitrification and/or DNRA by changing the Fe 2+ concentration in the surrounding sediment. We performed 15 N labeling laboratory experiments to measure these three processes using cable bacteria containing sediments from the Yarra River, Australia, and from Vilhelmsborg Sø, Denmark. Our results revealed that in the targeted systems, cable bacteria themselves did not perform significant rates of denitrification, DNRA, or nitrification. However, cable bacteria exhibited an important indirect effect, whereby they increased the Fe 2+ pool through iron sulfide dissolution. This elevated availability of Fe 2+ significantly increased DNRA and in some cases decreased denitrification. Thus, cable bacteria presence may affect the relative importance of DNRA in sediments and thus the extent by which bioavailable nitrogen is lost from the system.

Geochemistry and pH control of seepage from Ni-Cu rich mine tailings at Selebi Phikwe, Botswana - O. Sracek; B. Kříbek; M. Mihaljevič; V. Ettler; A. Vaněk; V. Penížek; J. Filip; F. Veselovský; Z. B. Bagai (Environmental Monitoring and Assessment, 2018)

Transient bottom water oxygenation creates a niche for cable bacteria in long‐term anoxic sediments of the Eastern Gotland Basin - Ugo Marzocchi; Stefano Bonaglia; Sebastiaan van de Velde; Per O. J. Hall; Andreas Schramm; Nils Risgaard‐Petersen; Filip J. R. Meysman (Environmental Microbiology, 2018)
Summary Cable bacteria have been reported in sediments from marine and freshwater locations, but the environmental factors that regulate their growth in natural settings are not well understood. Most prominently, the physiological limit of cable bacteria in terms of oxygen availability remains poorly constrained. In this study, we investigated the presence, activity and diversity of cable bacteria in relation to a natural gradient in bottom water oxygenation in a depth transect of the Eastern Gotland Basin (Baltic Sea). Cable bacteria were identified by FISH at the oxic and transiently oxic sites, but not at the permanently anoxic site. Three species of the candidate genus Electrothrix , i.e. marina , aarhusiensis and communis were found coexisting within one site. The highest filament density (33 m cm −2 ) was associated with a 6.3 mm wide zone depleted in both oxygen and free sulphide, and the presence of an electric field resulting from the electrogenic sulphur oxidizing metabolism of cable bacteria. However, the measured filament densities and metabolic activities remained low overall, suggesting a limited impact of cable bacteria at the basin level. The observed bottom water oxygen levels (

The effect of oxygen availability on long‐distance electron transport in marine sediments - Laurine D. W. Burdorf; Sairah Y. Malkin; Jesper T. Bjerg; Pieter van Rijswijk; Francis Criens; Anton Tramper; Filip J. R. Meysman (Limnology and Oceanography, 2018)
Cable bacteria are long, multicellular, filamentous bacteria that can conduct electrons over centimeter distances in marine and freshwater sediments. Recent studies indicate that cable bacteria are widely present in many coastal environments, where they exert a major influence on the biogeochemistry of the sediment. Their energy metabolism can be based on the aerobic oxidation of sulfide, and hence to better understand their natural occurrence and distribution, we examined the growth and activity of cable bacteria in relation to bottom water oxygenation. To this end, we conducted laboratory sediment incubations at four different O 2 levels in the overlying water (10%, 20%, 40%, and 100% air saturation). The abundance of cable bacteria was determined by fluorescence in situ hybridization, while their activity was assessed via microsensor profiling and geochemical pore‐water analysis. Cable bacteria did not develop in the 10% air saturation O 2 incubation but were present and active at all higher O 2 levels. These data show that microbial long‐distance electron transport can occur under a wide range of bottom water O 2 concentrations. However, the growth rate was notably slower at lower oxygen concentrations, suggesting a reduced metabolic activity of the population when the O 2 supply becomes restricted. Finally, in response to lower O 2 levels, cable bacteria filaments appear to partially emerge out of the sediment and extend into the overlying water, thus likely enhancing their oxygen supply.

Phosphorus Cycling and Burial in Sediments of a Seasonally Hypoxic Marine Basin - Fatimah Sulu-Gambari; Mathilde Hagens; Thilo Behrends; Dorina Seitaj; Filip J. R. Meysman; Jack Middelburg; Caroline P. Slomp (Estuaries and Coasts, 2018)

Marine‐terminating glaciers sustain high productivity in Greenland fjords - Lorenz Meire; John Mortensen; Patrick Meire; Thomas Juul‐Pedersen; Mikael K. Sejr; Søren Rysgaard; Rasmus Nygaard; Philippe Huybrechts; Filip J. R. Meysman (Global Change Biology, 2017)
Accelerated mass loss from the Greenland ice sheet leads to glacier retreat and an increasing input of glacial meltwater to the fjords and coastal waters around Greenland. These high latitude ecosystems are highly productive and sustain important fisheries, yet it remains uncertain how they will respond to future changes in the Arctic cryosphere. Here we show that marine‐terminating glaciers play a crucial role in sustaining high productivity of the fjord ecosystems. Hydrographic and biogeochemical data from two fjord systems adjacent to the Greenland ice sheet, suggest that marine ecosystem productivity is very differently regulated in fjords influenced by either land‐terminating or marine‐terminating glaciers. Rising subsurface meltwater plumes originating from marine‐terminating glaciers entrain large volumes of ambient deep water to the surface. The resulting upwelling of nutrient‐rich deep water sustains a high phytoplankton productivity throughout summer in the fjord with marine‐terminating glaciers. In contrast, the fjord with only land‐terminating glaciers lack this upwelling mechanism, and is characterized by lower productivity. Data on commercial halibut landings support that coastal regions influenced by large marine‐terminating glaciers have substantially higher marine productivity. These results suggest that a switch from marine‐terminating to land‐terminating glaciers can substantially alter the productivity in the coastal zone around Greenland with potentially large ecological and socio‐economic implications.

Zero-valent iron particles for PCB degradation and an evaluation of their effects on bacteria, plants, and soil organisms - Alena Ševců; Yehia S. El-Temsah; Jan Filip; Erik J. Joner; Kateřina Bobčíková; Miroslav Černík (Environmental Science and Pollution Research, 2017)

Semi-quantitative assessments of dextran toxicity on corneal endothelium: conceptual design of a predictive algorithm - Filip Filev; Ceprail Oezcan; Jana Feuerstacke; Stephan J. Linke; Birgit Wulff; Olaf J. C. Hellwinkel (Cell and Tissue Banking, 2017)

Sedimentary oxygen dynamics in a seasonally hypoxic basin - Dorina Seitaj; Fatimah Sulu‐Gambari; Laurine D. W. Burdorf; Alicia Romero‐Ramirez; Olivier Maire; Sairah Y. Malkin; Caroline P. Slomp; Filip J. R. Meysman (Limnology and Oceanography, 2017)
Seasonal hypoxia refers to the oxygen depletion that occurs in summer in the bottom water of stratified systems, and is increasingly observed in coastal areas worldwide. The process induces a seasonal cycle on the biogeochemistry of the underlying sediments, which remains poorly quantified. Here, we investigated the sedimentary oxygen consumption within Lake Grevelingen (The Netherlands), a saline coastal reservoir that is impacted by yearly recurrent bottom water hypoxia. Monthly sampling campaigns were conducted throughout 2012 at three sites along a depth gradient. Macrofauna sampling and sediment profile imaging demonstrated how summer hypoxia strongly impacts the benthic communities below 15 m of water depth. Benthic fluxes of oxygen, dissolved inorganic carbon, total alkalinity, and ammonium were determined by closed core incubations, while oxygen depth profiles were recorded by microsensor profiling of sediment cores. Our results reveal a pronounced seasonality in the sedimentary oxygen consumption. Low uptake rates in summer were caused by oxygen limitation, and resulted in the build‐up of an “oxygen debt” through the accumulation of reduced iron sulfides. Highest oxygen uptake rates were recorded in fall, linked to the reoxidation of the pool of iron sulfides in the top layer. However, uptake rates remained unexpectedly high during winter and early spring, likely associated with the oxidation of iron sulfides down to centimeters depth due to the electrogenic sulfur oxidation by cable bacteria. Overall, our results suggest that the sedimentary oxygen dynamic in seasonally hypoxic coastal systems is characterized by a strongly amplified “oxygen debt” dynamics induced by cable bacteria.

Electrogenic Sulfur Oxidation by Cable Bacteria in Bivalve Reef Sediments - Sairah Y. Malkin; Dorina Seitaj; Laurine D. W. Burdorf; Sil Nieuwhof; Silvia Hidalgo-Martinez; Anton Tramper; Naomi Geeraert; Henko De Stigter; Filip J. R. Meysman (Frontiers in Marine Science, 2017)

Expansion of Ashworthius sidemi in red deer and roe deer from the Lower Silesian Wilderness and its impact on infection with other gastrointestinal nematodes - Aleksander W. Demiaszkiewicz; Dorota Merta; Janusz Kobielski; Katarzyna J. Filip; Anna M. Pyziel (Acta Parasitologica, 2017)
Nematodes

Northern glacial refugia and altitudinal niche divergence shape genome‐wide differentiation in the emerging plant model Arabidopsis arenosa - Filip Kolář; Gabriela Fuxová; Eliška Záveská; Atsushi J. Nagano; Lucie Hyklová; Magdalena Lučanová; Hiroshi Kudoh; Karol Marhold (Molecular Ecology, 2016)
Quaternary climatic oscillations profoundly impacted temperate biodiversity. For many diverse yet undersampled areas, however, the consequences of this impact are still poorly known. In Europe, particular uncertainty surrounds the role of Balkans, a major hotspot of European diversity, in postglacial recolonization of more northerly areas, and the Carpathians, a debatable candidate for a northern ‘cryptic’ glacial refugium. Using genome‐wide SNP s and microsatellites, we examined how the interplay of historical processes and niche shifts structured genetic diversity of diploid Arabidopsis arenosa , a little‐known member of the plant model genus that occupies a wide niche range from sea level to alpine peaks across eastern temperate Europe. While the northern Balkans hosted one isolated endemic lineage, most of the genetic diversity was concentrated further north in the Pannonian Basin and the Carpathians, where it likely survived the last glaciation in northern refugia. Finally, a distinct postglacial environment in northern Europe was colonized by populations of admixed origin from the two Carpathian lineages. Niche differentiation along altitude‐related bioclimatic gradients was the main trend in the phylogeny of A. arenosa . The most prominent niche shifts, however, characterized genetically only slightly divergent populations that expanded into narrowly defined alpine and northern coastal postglacial environments. Our study highlights the role of eastern central European mountains not only as refugia for unique temperate diversity but also sources for postglacial expansion into novel high‐altitude and high‐latitude niches. Knowledge of distinct genetic substructure of diploid A. arenosa also opens new opportunities for follow‐up studies of this emerging model of evolutionary biology.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Internal parasitic fauna of elk (Alces alces) in Poland - Katarzyna J. Filip; Aleksander W. Demiaszkiewicz (Acta Parasitologica, 2016)
The abundance of elk (

Cold-water coral reefs and adjacent sponge grounds: hotspots of benthic respiration and organic carbon cycling in the deep sea - Cécile Cathalot; Dick Van Oevelen; Tom J. S. Cox; Tina Kutti; Marc Lavaleye; Gerard Duineveld; Filip J. R. Meysman (Frontiers in Marine Science, 2015)

Secondary arsenic minerals and arsenic mobility in a historical waste rock pile at Kaňk near Kutná Hora, Czech Republic - E. Kocourková-Víšková; J. Loun; O. Sracek; S. Houzar; J. Filip (Mineralogy and Petrology, 2015)

Magnetically-modified natural biogenic iron oxides for organic xenobiotics removal - I. Safarik; J. Filip; K. Horska; M. Nowakova; J. Tucek; M. Safarikova; H. Hashimoto; J. Takada; R. Zboril (International Journal of Environmental Science and Technology, 2015)

The dynamics of architectural complexity on coral reefs under climate change - Yves‐Marie Bozec; Lorenzo Alvarez‐Filip; Peter J. Mumby (Global Change Biology, 2015)
One striking feature of coral reef ecosystems is the complex benthic architecture which supports diverse and abundant fauna, particularly of reef fish. Reef‐building corals are in decline worldwide, with a corresponding loss of live coral cover resulting in a loss of architectural complexity. Understanding the dynamics of the reef architecture is therefore important to envision the ability of corals to maintain functional habitats in an era of climate change. Here, we develop a mechanistic model of reef topographical complexity for contemporary Caribbean reefs. The model describes the dynamics of corals and other benthic taxa under climate‐driven disturbances (hurricanes and coral bleaching). Corals have a simplified shape with explicit diameter and height, allowing species‐specific calculation of their colony surface and volume. Growth and the mechanical (hurricanes) and biological erosion (parrotfish) of carbonate skeletons are important in driving the pace of extension/reduction in the upper reef surface, the net outcome being quantified by a simple surface roughness index (reef rugosity). The model accurately simulated the decadal changes of coral cover observed in Cozumel (Mexico) between 1984 and 2008, and provided a realistic hindcast of coral colony‐scale (1–10 m) changing rugosity over the same period. We then projected future changes of Caribbean reef rugosity in response to global warming. Under severe and frequent thermal stress, the model predicted a dramatic loss of rugosity over the next two or three decades. Critically, reefs with managed parrotfish populations were able to delay the general loss of architectural complexity, as the benefits of grazing in maintaining living coral outweighed the bioerosion of dead coral skeletons. Overall, this model provides the first explicit projections of reef rugosity in a warming climate, and highlights the need of combining local (protecting and restoring high grazing) to global (mitigation of greenhouse gas emissions) interventions for the persistence of functional reef habitats.

Alteration of Root Growth by Lettuce, Wheat, and Soybean in Response to Wear Debris from Automotive Brake Pads - Misty D. Dodd; Stephen D. Ebbs; David J. Gibson; Peter Filip (Archives of Environmental Contamination and Toxicology, 2014)

Assessing anthropogenic impact on boreal lakes with historical fish species distribution data and hydrogeochemical modeling - Salar Valinia; Göran Englund; Filip Moldan; Martyn N Futter; Stephan J Köhler; Kevin Bishop; Jens Fölster (Global Change Biology, 2014)
Quantifying the effects of human activity on the natural environment is dependent on credible estimates of reference conditions to define the state of the environment before the onset of adverse human impacts. In Europe, emission controls that aimed at restoring ecological status were based on hindcasts from process‐based models or paleolimnological reconstructions. For instance, 1860 is used in Europe as the target for restoration from acidification concerning biological and chemical parameters. A more practical problem is that the historical states of ecosystems and their function cannot be observed directly. Therefore, we (i) compare estimates of acidification based on long‐term observations of roach ( Rutilus rutilus ) populations with hindcast pH from the hydrogeochemical model MAGIC; (ii) discuss policy implications and possible scope for use of long‐term archival data for assessing human impacts on the natural environment and (iii) present a novel conceptual model for interpreting the importance of physico‐chemical and ecological deviations from reference conditions. Of the 85 lakes studied, 78 were coherently classified by both methods. In 1980, 28 lakes were classified as acidified with the MAGIC model, however, roach was present in 14 of these. In 2010, MAGIC predicted chemical recovery in 50% of the lakes, however roach only recolonized in five lakes after 1990, showing a lag between chemical and biological recovery. Our study is the first study of its kind to use long‐term archival biological data in concert with hydrogeochemical modeling for regional assessments of anthropogenic acidification. Based on our results, we show how the conceptual model can be used to understand and prioritize management of physico‐chemical and ecological effects of anthropogenic stressors on surface water quality.

Understanding the Long Term Ecosystem Stability of a Fen Mire by Analyzing Subsurface Geology, Eco-Hydrology and Nutrient Stoichiometry – Case Study of the Rospuda Valley (NE Poland) - Ewa Jabłońska; Tomasz Falkowski; Jarosław Chormański; Filip Jarzombkowski; Stanisław Kłosowski; Tomasz Okruszko; Paweł Pawlikowski; Martin Theuerkauf; Martin J. Wassen; Wiktor Kotowski (Wetlands, 2014)

Geochemistry of mine tailings and behavior of arsenic at Kombat, northeastern Namibia - O. Sracek; M. Mihaljevič; B. Kříbek; V. Majer; J. Filip; A. Vaněk; V. Penížek; V. Ettler; B. Mapani (Environmental Monitoring and Assessment, 2014)

Changes in Soil Dissolved Organic Carbon Affect Reconstructed History and Projected Future Trends in Surface Water Acidification - Jakub Hruška; Pavel Krám; Filip Moldan; Filip Oulehle; Christopher D. Evans; Richard F. Wright; Jiří Kopáček; Bernard J. Cosby (Water, Air, & Soil Pollution, 2014)

Modeling Past and Future Acidification of Swedish Lakes - Filip Moldan; Bernard J. Cosby; Richard F. Wright (Ambio, 2013)

Opportunities for domesticating the African baobab (Adansonia digitata L.): multi-trait fruit selection - David J. Simbo; Sebastiaan De Smedt; Nina Van den Bilcke; Bruno De Meulenaer; John Van Camp; Veronique Uytterhoeven; Filip Tack; Roeland Samson (Agroforestry Systems, 2013)

The influence of pore‐water advection, benthic photosynthesis, and respiration on calcium carbonate dynamics in reef sands - Alexandra M. F. Rao; Lubos Polerecky; Danny Ionescu; Filip J. R. Meysman; Dirk de Beer (Limnology and Oceanography, 2012)
To investigate diel calcium carbonate (CaCO 3 ) dynamics in permeable coral reef sands, we measured pore‐water profiles and fluxes of oxygen (O 2 ), nutrients, pH, calcium (Ca 2+ ), and alkalinity (TA) across the sediment‐water interface in sands of different permeability at Heron Reef, Australia. Background flushing rates were high, most likely as a result of infaunal burrow irrigation, but flux chamber stirring enhanced pore‐water exchange. Light and pore‐water advection fueled high rates of benthic primary production and calcification in sunlit surface sediments. In the light, benthic photosynthesis and calcification induced surface minima in Ca 2+ and TA and peaks in pH and O 2 . Oxygen penetration depth in coarse sands decreased from ∼ 1.2 cm during the day to ∼ 0.6 cm at night. Total oxygen uptake (TOU) in dark chambers was three to fourteen times greater than diffusive uptake and showed a direct effect of pore‐water advection. Greater sediment oxygen consumption rates were observed in higher permeability sands. In the dark, TA release was not stimulated by increasing TOU because of a damping effect of pore‐water advection on metabolic CaCO 3 dissolution efficiency. On a daily basis, CaCO 3 undergoes net dissolution in Heron Reef sands. However, pore‐water advection can reverse the CaCO 3 budget and promote CaCO 3 preservation under the most energetic conditions.

Drivers of region-wide declines in architectural complexity on Caribbean reefs - Lorenzo Alvarez-Filip; J. A. Gill; N. K. Dulvy; A. L. Perry; A. R. Watkinson; I. M. Côté (Coral Reefs, 2011)

The antimicrobial action of low-molar-mass chitosan, chitosan derivatives and chitooligosaccharides on bifidobacteria - J. Šimůnek; I. Koppová; L. Filip; G. Tishchenko; G. BeŁżecki (Folia Microbiologica, 2010)

Differential modes of selection on the rhodopsin gene in coastal Baltic and North Sea populations of the sand goby, Pomatoschistus minutus - MAARTEN H. D. LARMUSEAU; KIM VANCAMPENHOUT; JOOST A. M. RAEYMAEKERS; JEROEN K. J. VAN HOUDT; FILIP A. M. VOLCKAERT (Molecular Ecology, 2010)

Quantifying Food Web Flows Using Linear Inverse Models - Dick van Oevelen; Karel Van den Meersche; Filip J. R. Meysman; Karline Soetaert; Jack J. Middelburg; Alain F. Vézina (Ecosystems, 2010)

Stability of high cell density brewery fermentations during serial repitching - Pieter J. Verbelen; Tinne M. L. Dekoninck; Sebastiaan E. Van Mulders; Sofie M. G. Saerens; Filip Delvaux; Freddy R. Delvaux (Biotechnology Letters, 2009)

To see in different seas: spatial variation in the rhodopsin gene of the sand goby ( Pomatoschistus minutus ) - MAARTEN H. D. LARMUSEAU; JOOST A. M. RAEYMAEKERS; KEVIN G. RUDDICK; JEROEN K. J. VAN HOUDT; FILIP A. M. VOLCKAERT (Molecular Ecology, 2009)
Aquatic organisms living in a range of photic environments require specific mechanisms to tune their visual pigments. Maximum absorbance (λ max ) of retinal rods in populations of the marine demersal sand goby, ( Pomatoschistus minutus ; Gobiidae, Teleostei) correlates with the local optic environment. It has been shown that this is not regulated through a physiological response by exchanging the rhodopsin chromophore. To test for evolutionary adaptation, the sequence of the rhodopsin ( RH1 ) gene was analysed in 165 Pomatoschistus minutus individuals from seven populations across its distribution range. Analysis showed a high level of intraspecific polymorphism at the RH1 gene, including nonsynonymous mutations on amino acids, known as spectral tuning sites. Population differentiation at these sites was in agreement with the observed differentiation in λ max values. Analyses of d N / d S substitution rate ratios and likelihood ratio tests under site‐specific models detected a significant signal of positive Darwinian selection on the RH1 gene. A strong discrepancy in differentiation was noticed between RH1 gene variation and the presumably neutral microsatellites and mitochondrial data. Samples did not cluster according to geographical or historical proximity with regards to RH1 , but according to the general photic conditions of the habitat environment of the sand goby. This study highlights the usefulness of sensory genes, like rhodopsin, for studying the characteristics of local adaptation in marine nonmodel organisms.

Distributional and demographic consequences of Pleistocene climate fluctuations for a marine demersal fish in the north‐eastern Atlantic - Maarten H. D. Larmuseau; Jeroen K. J. Van Houdt; Jef Guelinckx; Bart Hellemans; Filip A. M. Volckaert (Journal of Biogeography, 2009)
Aim The Pleistocene glaciations were the most significant historical event during the evolutionary life span of most extant species. However, little is known about the consequences of these climate changes for the distribution and demography of marine animals of the north‐eastern Atlantic. The present study focuses on the phylogeographic and demographic patterns of the sand goby, Pomatoschistus minutus (Teleostei: Gobiidae), a small marine demersal fish. Location North‐eastern Atlantic, Mediterranean, Irish, North and Baltic seas. Methods Analysis was carried out by sequencing the mtDNA cytochrome b gene of sand gobies from 12 localities throughout the species’ range, and using this information in combination with published data of allozyme markers and mtDNA control region sequences. Several phylogenetic methods and a network analysis were used to explore the phylogeographic pattern. The historical demography of P. minutus was studied through a mismatch analysis and a Bayesian skyline plot. Results Reciprocal monophyly was found between a Mediterranean Sea (MS) clade and an Atlantic Ocean (AO) clade, both with a Middle Pleistocene origin. The AO Clade contains two evolutionary significant units (ESUs): the Iberian Peninsula (IB) Group and the North Atlantic (NA) Group. These two groups diverged during Middle Pleistocene glacial cycles. For the NA Group there is evidence for geographic sorting of the ancestral haplotypes with recent radiations in the Baltic Sea, Irish Sea, North Sea and Bay of Biscay. The demographic histories of the Mediterranean Clade and the two Atlantic ESUs were influenced mainly by expansions dated as occurring during the Middle Pleistocene glaciations and post‐Eem, respectively. Main conclusions The pre‐LGM (Last Glacial Maximum) subdivision signals were not erased for P. minutus during the LGM. Middle Pleistocene glaciations yielded isolated and differently evolving sets of populations. In contrast to the case for most other taxa, only the northern Atlantic group contributed to the post‐glacial recolonization. The historical demography of Mediterranean sand gobies was influenced mainly by Middle Pleistocene glaciations, in contrast to that of the Atlantic populations, which was shaped by Late Pleistocene expansions.

Pillars of Hercules: is the Atlantic–Mediterranean transition a phylogeographical break? - TOMASO PATARNELLO; FILIP A. M. J. VOLCKAERT; RITA CASTILHO (Molecular Ecology, 2007)
The geological history of the Mediterranean Sea, its hydrography and connection with the Atlantic Ocean have been well documented. Despite a wealth of historical and oceanographic data, the Atlantic–Mediterranean transition remains controversial at the biological level as there are discordant results regarding the biogeographical separation between the Atlantic and Mediterranean biota. The opening of the Strait of Gibraltar at the end of the Messinian Salinity Crisis (some 5.33 million years ago), removed the land barrier that impeded the marine biota allowing it to disperse freely into the Mediterranean Sea. However, present day genetic patterns suggest a limitation to gene flow for some marine species, preventing population admixture. In the last few years, a large number of studies have challenged the hypothesis of the Strait of Gibraltar representing a phylogeographical break. A review of more than 70 papers reveals no obvious relationship between either dispersal ability or life history, and observed patterns of partial or complete genetic isolation between Atlantic and Mediterranean populations. We re‐analysed a selection of this large body of data (20 studies in total) in order to provide a homogeneous and coherent view on the generality of the phylogeographical patterns and the presence of a phylogeographical barrier. This offered the opportunity to summarize the state of the art on this matter and reach some general conclusions on the evolutionary history across the Atlantic–Mediterranean range. Geographically, some species in the transition zone showed step changes of allele frequencies associated with the Almeria‐Oran Front rather than with the Strait of Gibraltar itself. A major part of the data describe evolutionary events well within the time frame of the Quaternary age as very few taxa pre‐date closure of the Tethys Sea. Results point to a combined signature of vicariance, palaeoclimate fluctuation and life‐history traits on the Atlantic–Mediterranean phylogeographical patterns. Principal component analysis failed to show any particular association between biological traits and genetic variables. It would argue that organismal determinism may play a far less significant role than marine biogeographers have generally believed.

Synthesis and In vitro Biological Activity of Cyclic Lipophilic χ-Conotoxin MrIA Analogues - Zoltan Dekan; Filip A. Paczkowski; Richard J. Lewis; Paul F. Alewood (International Journal of Peptide Research and Therapeutics, 2007)

Divergent selection as revealed by P ST and QTL‐based F ST in three‐spined stickleback ( Gasterosteus aculeatus ) populations along a coastal‐inland gradient - JOOST A. M. RAEYMAEKERS; JEROEN K. J. VAN HOUDT; MAARTEN H. D. LARMUSEAU; SARAH GELDOF; FILIP A. M. VOLCKAERT (Molecular Ecology, 2007)
Three measures of divergence, estimated at nine putatively neutral microsatellite markers, 14 quantitative traits, and seven quantitative trait loci (QTL) were compared in eight populations of the three‐spined stickleback ( Gasterosteus aculeatus L.) living in the Scheldt river basin (Belgium). Lowland estuarine and polder populations were polymorphic for the number of lateral plates, whereas upland freshwater populations were low‐plated. The number of short gill rakers and the length of dorsal and pelvic spines gradually declined along a coastal‐inland gradient. Plate number, short gill rakers and spine length showed moderate to strong signals of divergent selection between lowland and upland populations in comparison between P ST (a phenotypic alternative for Q ST ) and neutral F ST . However, such comparisons rely on the unrealistic assumption that phenotypic variance equals additive genetic variance, and that nonadditive genetic effects and environmental effects can be minimized. In order to verify this assumption and to confirm the phenotypic signals of divergence, we tested for divergent selection at the underlying QTL. For plate number, strong genetic evidence for divergent selection between lowland and upland populations was obtained based on an intron marker of the Eda gene, of which the genotype was highly congruent with plate morph. Genetic evidence for divergent selection on short gill rakers was limited to some population pairs where F ST at only one of two QTL was detected as an outlier, although F ST at both loci correlated significantly with P ST . No genetic confirmation was obtained for divergent selection on dorsal spine length, as no outlier F ST s were detected at dorsal spine QTL, and no significant correlations with P ST were observed.

Prevention of infection transmission during stem cell transplantation - M. Bláha; P. Měřička; V. Štěpánová; M. Špliňo; J. Malý; L. Jebavý; P. Žák; M. Cermanová; S. Filip; M. Blažek; V. Řeháček (Folia Microbiologica, 2006)

Immobilized yeast cell systems for continuous fermentation applications - Pieter J. Verbelen; David P. De Schutter; Filip Delvaux; Kevin J. Verstrepen; Freddy R. Delvaux (Biotechnology Letters, 2006)

Evidence for isolation by time in the European eel ( Anguilla anguilla L.) - GREGORY E. MAES; J. M. PUJOLAR; B. HELLEMANS; FILIP A. M. VOLCKAERT (Molecular Ecology, 2006)
Life history traits of highly vagile marine species, such as adult reproductive success and larval dispersal, are strongly determined by oceanographic and climatic forces. Nevertheless, marine organisms may show restricted dispersal in time and space. Patterns of isolation by distance (IBD) have been repeatedly observed in marine species. If spawning time is a function of geographical location, temporal and spatial isolation, can easily be confounded or misinterpreted. In this study, we aimed at discriminating between various forces shaping the genetic composition of recruiting juveniles of the European eel ( Anguilla anguilla L.). By controlling for geographical variation, we assessed temporal variation and tested for possible isolation by time (IBT) between recruitment waves within and between years. Using 12 polymorphic allozyme and six variable microsatellite loci, we show that genetic differentiation was low ( F ST = 0.01–0.002) and significant between temporal samples. Regression analysis between genetic and temporal distance, was consistent with a subtle interannual pattern of IBT. Our data suggest that the population dynamics of the European eel may be governed by a double pattern of temporal variance in genetic composition: (i) a broad‐scale IBT of spawning cohorts, possibly as a consequence of the large migration loop in anguillids and strong variance in annual adult reproductive contribution; and (ii) a smaller‐scale variance in reproductive success (genetic patchiness) within cohorts among seasonally separated spawning groups, most likely originating from fluctuating oceanic and climatic forces. The consistency of both mechanisms remains to be verified with fine‐scale analyses of both spawning/migrating aged adults and their offspring to confirm the stochastic/deterministic nature of the IBT pattern in eel.

Genetic diversity and population history of the migratory catfishes Pangasianodon hypophthalmus and Pangasius bocourti in the Cambodian Mekong River - Nam SO; Jeroen K J VAN HOUDT; Filip A M VOLCKAERT (Fisheries Science, 2006)

Contribution of serotonin (5-HT) 5-HT2 receptor subtypes to the discriminative stimulus effects of cocaine in rats - Malgorzata Filip; Marcy J. Bubar; Kathryn A. Cunningham (Psychopharmacology, 2006)

Crystal chemistry and OH defect concentrations in spodumene from different granitic pegmatites - J. Filip; M. Novák; A. Beran; R. Zbořil (Physics and Chemistry of Minerals, 2006)

Gluconobacter oxydans NAD-dependent, D-fructose reducing, polyol dehydrogenases activity: screening, medium optimisation and application for enzymatic polyol production - Sofie Parmentier; Joeri Beauprez; Filip Arnaut; Wim Soetaert; Erick J. Vandamme (Biotechnology Letters, 2005)

1H NMR structure of the heme pocket of HNO-myoglobin - Filip Sulc; Everly Fleischer; Patrick J. Farmer; Dejian Ma; Gerd N. La Mar (JBIC Journal of Biological Inorganic Chemistry, 2003)

Expression and chromosomal localization of the Requiem gene - Theodore G. Gabig; Colin D. Crean; Alison Klenk; Haiyan Long; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Danielle Quincey; Fabienne Parente; Françoise Lespinasse; Georges F. Carle; Patrick Gaudray; et al. (Mammalian Genome, 1998)

Einflu von Montmorillonit auf die Bildung von Biomasse und Stoffwechselzwischenprodukten durch einige Mikroorganismen - K. Haider; Z. Filip; J. P. Martin (Archives of Microbiology, 1970)